CLINICO-THERAPEUTIC MANAGEMENT OF COLOSTRUM INDIGESTION IN MURRAH BUFFALO - M.F.M.F Siddiqui; M.P. Sakhare; A.M. Syed; S.R. Shaikh; M.M. Raut; P.M. Padole (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A six year old female buffalo was presented with history ofparturition before 4 days and accidental feeding of about 4 litres own colostrum by the owner. Clinical examination revealed anorexia, circling, excitation and wandering behavior, mucoid hard sticky feces, absence of water intake and ruminal atony. pH of ruminal fluid was 8.5. The buffalo was successfully treated with vinegar, multivitamin, chlorpheneramine maleate, calcium sulphate, magnesium sulphate and fluid therapy and recovery was seen on 3rd day. In conclusion, colostrum feeding in adult buffalo can cause alkaline indigestion which can be successfully treated with vinegar and supportive fluid therapy.